Benzothiazole‐Phenothiazine Conjugate Based Molecular Probe for the Differential Detection of Glycated Albumin. Issue 3 (26th January 2021) - Kumar, Ashish; Datta, Lakshmi Priya; Samanta, Sourav; Arora, Harshit; Govindaraju, Thimmaiah
Abstract: Glycation of albumin proteins is considered the pathophysiological hallmark of several chronic fatal disorders, including diabetes mellitus (DM) and Alzheimer's disease (AD). The optical detection of glycated albumin is a simple and cost‐effective tool with diagnostic implications for DM and AD. Herein, we developed a cyano derivative of the benzothiazole‐phenothiazine conjugate (TCN P) ‐based far‐red fluorescence probe for the differential detection of glycated bovine serum albumin (BSAG ) over native BSA and oxidized BSA (BSAO ). The selective fluorescence enhancement of TCN P in the presence of native BSA and BSAO and significant quenching in the presence of BSAG account for the distinct interaction between the probe and different structural variants of BSA. The high photostability and differential response towards native BSA and BSAG infer that TCN P is a potential molecular tool to assess the glycation induced structural changes of albumins. Abstract :